Proverbs and Figurative Expressions as Markers of Feminist Ideology in Selected Femi Osofisan Plays - Olusola, Akinmameji Oluwayemisi (Linguistik Online, 2020)
Literature abounds on the way gender issues are foregrounded in both literary and non-literary texts. Many of these studies, especially from the linguistic perspective, fail to pay attention to how proverbs and figurative expressions are used to expose feminist ideology in discourse. This study, therefore, considers the way these cultural elements are used to ex-press the feminist beliefs of Femi Osofisan in some of his drama texts to lend credence to the argument that every genre of text and talk is capable of bearing ideological nuances. The study deploys Norman Fairclough’s socio-cultural model of CDA which incorporates aspects of Systemic Functional Grammar (SFG) as theoretical model. Three of Osofisan’s drama texts, which mostly express his feminist tendencies; Morountodun, YungbaYungba and the Dance Contest and Tegonni: An African Antigone are purposively sampled to explain the expressive capabilities of women. Proverbs and figurative expressions are subjected to descriptive linguistic analysis to bring out the underlying gender rhetoric. Osofisan projects women’s ability to use proverbs and figures of speechto express power. There is the overrid-ing feminist ideology of women as expressive and dynamic in the texts.